Stingless bee foraging behavior and pollen resource use in oil palm and rubber plantations in Sumatra - Rosi Fitri Ramadani; Rika Raffiudin; Nunik Sri Ariyanti; Siria Biagioni; Erin Treanore; Hermann Behling (Perhimpunan Entomologi Indonesia, 2021)
Land transformation in the tropical rainforests to monoculture plantations leads to biodiversity loss and abiotic change. In the oil palm and rubber plantations of Sumatra, we explored the foraging behavior of stingless bees Lepidotrigona terminata, Sundatrigona moorei, and Tetragonula drescheri. Pollen was collected from bees returning to the nest to investigate the floral resources collected by bees inside and outside research plots from both types of plantations. Foraging behavior in both plantations showed an increase in the number of individuals returning to the nest with pollen as the morning progressed, followed by a gradual decrease in the afternoon. The foraging behavior of each stingless bee species was influenced by different environmental factors. While the activity of S. moorei was positively correlated with humidity, the activity of L. terminate was negatively correlated with temperature. We found that a single pollen load was dominated by a single plant taxon in all bee species in both plantations. All pollen collected in the rubber plantation was from Hevea brasiliensis, suggests that rubber is a potential pollen resource. However, in the oil palm plantation, Asteraceae pollen was the dominant taxon collected by both L. terminata and S. moorei. The comparison to the plant inventories in the plots suggests that almost half of the pollen collected by these two species in the oil palm hives was from outside the plantations, probably in forested patches and surrounding gardens. Finally, based on multivariate analyses, we found no competition for these floral resources between L. terminata and S. moorei.